Should Cannabis as Medicine be Specifically Regulated? - Gunawan Widjaja (Pharmacology and Clinical Pharmacy Research)
In 2017, a patient case in Sangau, West Kalimantan, involving a women with syringomyelia has drawn public attention. The case ended with the arrest of her husband who cultivated Cannabis to treat her disease. Currently, Indonesian regulation classifies Cannabis as the first group of narcotics which are prohibited to be used as medicine. This research aimed to ellaborate whether Cannabis as medicine should be specifically regulated. Data source was national and international regulation on narcotics and scientific evidence regarding medical benefit of Cannabis The data was obtained from literature search with following keywords; regulation of Cannabis, medical use of Cannabis, Cannabis medicine. Analysis was conducted using qualitative approach. The results of this study showed that Indonesian regulation regarding Cannabis is associated with International Convention on narcotics. Evidence-based data on Cannabis application in medical treatment have been extensively studied. Given beneficial effect of Cannabis to treat many diseases, several countries have already regulated the use of Cannabis for medical purpose. In conclusion, it is worth to consider a specific regulation for medical Cannabis in Indonesia, given its beneficial utilization to treat certain diseases.Key words: Regulation, Cannabis, medical Cannabis, syringomelia